Copper chalcogenide materials as photothermal agents for cancer treatment. Issue 5 (22nd January 2020) - Liu, Kun; Liu, Kai; Liu, Junchao; Ren, Qilong; Zhao, Zhen; Wu, Xiaoyu; Li, Dalin; Yuan, Fukang; Ye, Kaichuang; Li, Bo
Abstract : This work for the first time reviews the recent research progress of copper-based chalcogenide photothermal materials. Abstract : Copper-based chalcogenide nanomaterials have made tremendous progress for cancer theranostics due to their simple preparation, low cost, stable performance, and easy functionalization. But a systematic review and analysis about them does not exist. Therefore, we offer an account, mainly focusing on the design and functionalization of the copper-based chalcogenide nanomaterials for cancer theranostics, aiming to briefly demonstrate the design and concepts, summarize some of the past studies and analyze the development trends in the copper-based chalcogenide nanomaterials for clinical application.